Nature of electrophilic oxygen: insights from periodic density functional theory investigations - Kenge, Nivedita; Pitale, Sameer; Joshi, Kavita (Surface Science, 2019)
Increasing demand of ethylene oxide and the cost of versatile chemical ethene has been a driving force for understanding mechanism of epoxidation to develop highly selective catalytic process. Direct epoxidation is a proposed mechanism which in theory provides 100% selectivity. A key aspect of this mechanism is an electrophilic oxygen (O-ele) species forming on the Ag surface. In the past two and half decades, large number of theoretical and experimental investigations have tried to elucidate formation of O-ele, on Ag surface with little success. Equipped with this rich literature on Ag-O interactions, we investigate the same using periodic DFT calculations to further understand how silver surface and oxygen interact with each other from a chemical standpoint. Based on energetics, Lowdin charges, topologies and pdos data described in this study, we scrutinize the established notions of O-ele. Our study provides no evidence in support of O-ele, being an atomic species nor a diatomic molecular species. In fact, a triatomic molecular species described in this work bears multiple signatures which are very convincing evidence for considering it as the most sought for electrophilic entity.
Keywords: Ag(100); DFT; Electrophilic; epoxidation; Nucleophilic oxygen

Mixed metal oxide: a new class of catalyst for methanol activation - Mehta, Shweta; Agarwal, Sheena; Kenge, Nivedita; Mekala, Siva Prasad; Patil, Vipul; Raja, T.; Joshi, Kavita (Applied Surface Science, 2020)
In this work, we propose a mixed metal oxide as a catalyst and demonstrate it's ability to not only activate the MeOH molecule upon adsorption but also dissociate O-H and one of it's C-H bonds. MeOH activation is compared on two prominent facets of ZnAl(2)O(4 )viz. (2 2 0) and (31 1). While spontaneous O-H bond dissociation is observed on both facets, C-H bond dissociates only on the (3 1 1) surface. Multiple factors like atomic arrangement and steps on the surface, coordination of surface atoms, and their effective charges have a combined effect on MeOH activation. The (3 1 1) surface offers higher catalytic activity in comparison with (2 2 0) surface. Having a stepped surface, availability of multiple sites, and variation in the charge distribution are some of the reasons for better catalytic performance of (3 1 1) facet. Effect of orientation of MeOH with respect to the surface adds both, information and complexity to the problem. Observations pertinent to understanding this effect are also reported. A detailed analysis of atomic arrangement on the two surfaces provides a rationale as to why MeOH gets dissociated spontaneously on the mixed metal oxide. The promising results reported here opens up a new class of catalyst for research.
Keywords: DFT; MeOH; Spontaneous dissociation; ZnAl2O4

Role of facet in the competitive pathway of ethylene epoxidation - Nair, Aathira; Kenge, Nivedita; Joshi, Kavita (Surface Science, 2022)
Ethylene epoxide (EtO) is used as raw material for a broad range of products from pharmaceuticals and plastics to paints and adhesives. Although the reaction of ethylene interacting with preadsorbed oxygen on Ag surface is known for decades, the underlying mechanism of EtO formation is not completely understood. Successful investigation of oxametallacycle (OMC) intermediate common to selective as well as non-selective pathways has ensured at least 50% selectivity. The current study brings out the electronic signatures of distinct conformers of OMC stabilised on two different facets of Ag viz. (100) and (111). There are subtle differences between OMC conformers observed on these two facets with near-eclipsed on Ag(100) and near-staggered on Ag(111). A detailed analysis of Ag-O, C-O, C-C, and Ag-C interactions along with projected Density of States (pDOS) and projected Crystal Orbital Hamilton Population (pCOHP) imply towards ring closure on Ag(100) and hydrogen transfer on Ag(111). Finally, our understanding based on electronic and structural signatures are backed up by activation barriers computed through NEB calculations. Activation barrier for EtO is lower on (100) as compared to (111) facet. Thus, our study sheds light on how these differences between OMC affect the selectivity towards EtO.
Keywords: Ag(100); Ag(111); DFT; epoxidation; Ethylene Oxide (EtO); OMC